Preparation of insensitive composites based on penta erythritol tetra nitrate particles coated with carbon black- Triton X114 by a solvent/non-solvent process via Taguchi design optimization - Babaee, Saeed; Pourmortazavi, Seied Mahdi; Saberi Lemraski, Masoomeh (HEMIJSKA INDUSTRIJA (Chemical Industry), 2019)
One way to reduce sensitivity and also to add special properties to explosives is to perform coating that depends on either the coating agent type or the usage process. In this work, the insensitive composite of penta erythritol tetra nitrate (PETN) was prepared with carbon black (CB) and Triton X-114 (TX114) by a solvent/non-solvent method. Taguchi experimental design (orthogonal array, L9) with using the impact sensitivity (H50) as a response was applied for the process optimization. Effects of the CB mass fraction, solvent flowrate, surfactant type and surfactant concentration were evaluated and the results were quantified by the analysis of variance (ANOVA). The ANOVA analysis predicted that the best H50 was 67.4 ± 1.5 cm for the optimum synthesis conditions of 5.0 wt% CB, 1 mL min-1 flowrate, and TX114 as a surfactant at a concentration of 2.0´10-3 mol L-1. The experimentally determined value of H50 was 68.0 ± 0.5   cm, which is in good agreement with the predicted value. Finally, thermal analysis and vacuum stability test were applied to the synthesized composite indicating that CB and TX114 are thermally adaptable and chemically compatible with PETN.